Alokacja podatku dochodowego w spółkach kapitałowych w Polsce - prezentacja wyników badań - Sokalski, Jarosław (Income Tax Allocation in Capital Companies in Poland - the Results of Research, 2005)
Poland is characterized by high level of considerable differences between income tax law and accounting regulations. The article presents the results of research concentrated on selected group of companies (excluding public companies traded on the Warsaw Stock Exchange) and auditors. In spite of observed domination of law regulations in contentious issues with accounting the biggest part of above mentioned entities allocates income tax. It is espeferred tax directly in equity and deferred tax assets for tax losses, which is relatively new in Polish accounting. Summarizing: the companies recognize income tax allocation as an essential instrument to reach the main aim of accounting - presentation of company according to true and fair view concept.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 307-318